Pengaruh Pemasaran Media Sosial, Ulasan Online Konsumen, dan Persepsi Harga terhadap Minat Beli Produk Somethinc: Pada Generasi Z di Kota Semarang dengan Citra Merek sebagai Variabel Mediasi - Dewi Septiyani; Heri Prabowo; Rauly Sijabat (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth, encouraging local brands such as Somethinc to continuously innovate in their marketing strategies. This study aims to analyze the influence of social media marketing, online consumer reviews, and price perception on purchase intention of Somethinc products, especially among Generation Z in Semarang City. Brand image is tested as a mediating variable in the relationship between these three factors and purchase intention. This study uses a quantitative approach with a survey method of 399 Generation Z respondents who are Somethinc product users. The sample was determined using a purposive sampling technique and refers to the Slovin formula. Data processing and analysis were carried out using path analysis techniques with the help of SmartPLS 3 software. The results show that social media, online consumer reviews, and price perception have a positive and significant influence on Somethinc's brand image. In addition, brand image is also proven to have a positive and significant influence on consumer purchase intention. However, social media marketing does not directly have a significant influence on purchase intention. In contrast, online consumer reviews and price perception have a positive and significant direct influence on purchase intention. Brand image acts as a strong mediator in strengthening the influence of these three independent variables on purchase intention. These findings suggest that Something needs to strengthen its engaging and interactive social media content strategy, collaborate with influencers, and build two-way communication to enhance its brand image, which will ultimately drive purchasing interest from young consumers.